2021
DOI: 10.2131/jts.46.487
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to cigarette smoke exacerbates polyhexamethylene guanidine-induced lung fibrosis in mice

Abstract: Cigarette smoke (CS) is the leading cause of chronic pulmonary diseases, including lung cancer, chronic obstructive pulmonary disease, and pulmonary fibrosis. In this study, we aimed to investigate the effects of repeated CS exposure on polyhexamethylene guanidine (PHMG)-induced pulmonary fibrosis in mice. A single intratracheal instillation of 0.6 mg/kg PHMG enhanced the immune response of mice by increasing the number of total and specific inflammatory cell types in the bronchoalveolar lavage fluid. It induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Rats repeatedly exposed to cigarette smoke for 13 weeks displayed increased alveolar macrophages, pigmented and thickened alveolar walls, as well as hypertrophy/hyperplasia in the lungs 40 . In addition, it was confirmed that alveolar macrophage infiltration into the lungs of rats was mainly observed after repeated cigarette smoke exposure for 2 or 4 weeks 31,41 . The results of this study predict that repeated injection of WCSCs using ITI induced lung inflammation and damage similar to inhalation exposure.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Rats repeatedly exposed to cigarette smoke for 13 weeks displayed increased alveolar macrophages, pigmented and thickened alveolar walls, as well as hypertrophy/hyperplasia in the lungs 40 . In addition, it was confirmed that alveolar macrophage infiltration into the lungs of rats was mainly observed after repeated cigarette smoke exposure for 2 or 4 weeks 31,41 . The results of this study predict that repeated injection of WCSCs using ITI induced lung inflammation and damage similar to inhalation exposure.…”
Section: Discussionsupporting
confidence: 67%
“…40 In addition, it was confirmed that alveolar macrophage infiltration into the lungs of rats was mainly observed after repeated cigarette smoke exposure for 2 or 4 weeks. 31,41 The results of this study predict that repeated injection of WCSCs using ITI induced lung inflammation and damage similar to inhalation exposure. Our findings provide insight into the pulmonary inflammation response.…”
Section: Discussionmentioning
confidence: 71%
“…However, no clinical evidence showed how ETS exposure contributes to fibrogenesis development [ 12 , 32 ]. Recent animal studies have described that CS exacerbates the fibrotic progression induced by different causes such as bleomycin, lipopolysaccharides (LPS), polyhexamethylene guanidine, and influenza A virus (IAV) [ 3 , 6 , 7 , 33 , 34 ]. CS exposure followed by bleomycin administration showed significantly increased hydroxyproline and collagen deposition compared to bleomycin alone [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages, a crucial play in chronic diseases, can be adversely affected by CS, causing dysfunction . Repeated exposure to CS can also lead to macrophage infiltration and contribute to organ fibrosis development . Macrophages are vital for immunity and protecting the body from pathogens.…”
Section: Discussionmentioning
confidence: 99%